Paulo Leminski : fabriquer une poésie à la portée de tout le monde - Mario Cámara (Brésil(s))
This article takes a three-pronged approach to Paulo Leminski's poetic project. First, it looks at the poet's search for an articulation between the experimentation and discipline proposed by the concrete poets (Haroldo de Campos, Augusto de Campos and Décio Pignatari) and the pop and counter-cultural proposition of the tropicalist music movement (Caetano Veloso and Gilberto Gil, in particular). Secondly, it argues that Leminski derives this articulation from the form of « haïku » and « post-haïku », a poetic form that enables him to combine rigor and counter-culture. Finally, Leminski's legacy for the present day is examined, taking into account what his work evokes.